The Role Of Lio Custom In The Government Of Wologai Tengah Village, Detusoko District, Ende Regency, NTT - Satban, Martinus (Syntax Corporation Indonesia, 2023)
Villages in accordance with their original essence and various understandings of them in various perspectives are interesting to research and study. It is even more interesting when the village as a socio-cultural community is drawn into a socio-political community unit and made into a government unit. Organizing villages as one of the units of government in the Indonesian government system has experienced a long and increasingly interesting historical journey. Understanding the village as a legal community unit in its socio-cultural ties as a base for the formation of the village as one of the units of government in the Indonesian government system is absolute. The customs that live, attached to the journey of civilization of indigenous peoples actually contain many values that are expected to be a preference in arranging them into a village government unit. The right way and method will become a model and approach in organizing village governance based on the values of customs that apply in the indigenous community, of course, depending on how to give a role or customs play a role in its own socio-cultural position in village governance. In the end, customs that live in the hearts of indigenous peoples, have always been a way of life, lived diligently, have turned out to be a resource and potential, which contributes effectively in various aspects of the lives of indigenous peoples and is not easily eroded by the invasion of other systems outside it.